In situ SU-8 silver nanocomposites - Fischer, Søren V.; Uthuppu, Basil; Jakobsen, Mogens H. (Beilstein Journal of Nanotechnology, 2015)
Nanocomposite materials containing metal nanoparticles are of considerable interest in photonics and optoelectronics applications. However, device fabrication of such materials always encounters the challenge of incorporation of preformed nanoparticles into photoresist materials. As a solution to this problem, an easy new method of fabricating silver nanocomposites by an in situ reduction of precursors within the epoxy-based photoresist SU-8 has been developed. AgNO3 dissolved in acetonitrile and mixed with the epoxy-based photoresist SU-8 forms silver nanoparticles primarily during the pre- and post-exposure soft bake steps at 95 °C. A further high-temperature treatment at 300 °C resulted in the formation of densely homogeneously distributed silver nanoparticles in the photoresist matrix. No particle growth or agglomeration of nanoparticles is observed at this point. The reported new in situ silver nanocomposite materials can be spin coated as homogeneous thin films and structured by using UV lithography. A resolution of 5 µm is achieved in the lithographic process. The UV exposure time is found to be independent of the nanoparticle concentration. The fabricated silver nanocomposites exhibit high plasmonic responses suitable for the development of new optoelectronic and optical sensing devices.
Keywords: functional photoresist; in situ synthesis; metal nanoparticles; micro and nanofabrication; nanocomposite

(untitled) - Daniel, M.-C.; Astruc, D. (Chem. Rev., 2004)

Metal Nanoparticles: Synthesis, Characterization, and Applications - Fedlheim, D. L.; Foss, C. A. (Overview, 2002)

(untitled) - Yaklin, M. A.; Duxbury, P. M.; Mackay, M. E. (Soft Matter, 2008)

(untitled) - Wei, G.; Bhushan, B.; Ferrell, N.; Hansford, D. (J. Vac. Sci. Technol., A, 2005)

(untitled) - Gray, B. (J. Electrochem. Soc., 2014)

(untitled) - Chung, D.; Khosla, A.; Gray, B. L.; Parameswaran, A. M.; Ramaseshan, R.; Kohli, K. (J. Electrochem. Soc., 2014)

(untitled) - Mizeikis, V.; Juodkazis, S.; Tarozaitė, R.; Juodkazyté, J.; Juodkazis, K.; Misawa, H. (Opt. Express, 2007)

Proceedings of SPIE: Advances in Resist Technology and Processing XII - LaBianca, N. C.; Gelorme, J. D. (High-aspect-ratio resist for thick-film applications, Santa Clara, CA, 19.2.1995)

(untitled) - Serbin, J.; Ovsianikov, A.; Chichkov, B. (Opt. Express, 2004)

(untitled) - Nemani, K. V.; Moodie, K. L.; Brennick, J. B.; Su, A.; Gimi, B. (Mater. Sci. Eng., C, 2013)

(untitled) - Chen, Y.-S.; Tal, A.; Kuebler, S. M. (Chem. Mater., 2007)

(untitled) - Flack, W. W.; Soong, D. S.; Bell, A. T.; Hess, D. W. (J. Appl. Phys., 1984)

(untitled) - Jiguet, S.; Bertsch, A.; Hofmann, H.; Renaud, P. (Adv. Eng. Mater., 2004)

(untitled) - Jiguet, S.; Bertsch, A.; Hofmann, H.; Renaud, P. (Adv. Funct. Mater., 2005)

(untitled) - Keller, S.; Blagoi, G.; Lillemose, M.; Haefliger, D.; Boisen, A. (J. Micromech. Microeng., 2008)

Absorption and Scattering of Light by Small Particles - Bohren, C. F.; Huffmann, D. R. (Wiley-VCH, 1983)

(untitled) - Fang, Y. (J. Chem. Phys., 1998)

(untitled) - del Campo, A.; Greiner, C. (J. Micromech. Microeng., 2007)